OPTIMALISASI PERPUSTAKAAN RPTRA BERBASIS INKLUSI SOSIAL UNTUK MASYARAKAT KEPULAUAN SERIBU YANG MENGALAMI EKSKLUSI SOSIAL - Dian Novita Fitriani; Niswa Nabila Sri Bintang Alam (Jurnal IPI (Ikatan Pustakawan Indonesia), 2019)
Objective: 1) to identify the demography of the Kepulauan Seribu people who experienced social exclusion, 2) to know the role of the RPTRA library for Kepulauan Seribu community and 3) to formulate the optimized social inclusion RPTRAlibrary for Kepulauan Seribu community. Method: The research method is descriptive qualitative with a critical ethnographic approach. The data in this study are still in the form of preliminary data. Data collection carried out through 7 days of participant observation on UntungJawa Island and interviews. The technique of determining the informant was purposive sampling. Results: Kepulauan Seribu as a small archipelago with minimal transportation, means of communication made Kepulauan Seribu isolated from other regions. In addition, the poverty rate in the Thousand Islands shows the highest number compared to other districts / cities. While Human Development Index shows the lowest number. This shows that the people of the Thousand Islands experienced social exclusion. To overcome various social exclusion problems, the concept of social inclusion is a solution. One of the institutions that needs to pay attention on social inclusion is library. One facility that has a library is RPTRA. But so far the RPTRA library is still focused on children. Even though one of RPTRA's visions is to improve the economy of the community. Therefore, the RPTRA library needs to optimized to become a social inclusion based library to achieve community welfare and do the full vision of RPTRA.